Nurturing a Rural Community by Introducing Coconut Sap Sugar Technology in a Philippines Remote Location - Erlene C. Manohar (International Coconut Community, 2010)
The farm level technology of processing coconut sap sugar from toddy is a social enterprise which created a significant change in the livelihood of the people dependent on the coconut trees in Aroman, Carmen, North Cotabato. Technical skills acquired through training, appropriate facilities, capital and access to market are the key factors in developing a farm-level technology were used to emerge a commercially viable social enterprise. Indicators of change were gauged through change in income, equality of income distribution and preference in household expenditure. The increased income was disposed of by an increase in the cost of living and altered purchasing preferences. Significantly, the highest change of expenditure was on food and less in education notably 25.81 and 20.44 percent. In the case of income distribution, even with 2.39 percent increase on the percent share of the lowest 20% income group, there was an improvement in the income of the farmer-processor “after” the project implementation. But still, the community remains within the inequitable income distribution status group. It is expected that another year of business will have further favourable impact on income distribution among the respondents.